CULTURAL GENRE AND INDIAN KNOWLEDGE TRADITION - Pandey, Krishna Chand (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Broadly speaking, culture can be called the way of life of a country or a people. Scholars of an-thropology and sociology consider culture as a manifest characteristic of the way of life of a historical people and society and target it more or less, sometimes coherently and sometimes incoherently, in all dimensions of life such as customs, behavior, knowledge, science, arts and crafts etc. From their point of view, organized society is the basic entity, culture is its depend-ent characteristics of values, limits and rules, symbols and duties.